The impact of information-seeking behaviour and electronic information resource utilization on academic performance among Nigerian undergraduate students - Ahmed, Mohammed Bello; Wan Mokhtar, Wan Nor Haliza; Baharuddin, Mohammad Fazli (Faculty of Information Management, 2024)
In today's rapidly changing world, technological innovation has significantly impacted various disciplines including universities libraries. This study investigates the influence of undergraduate students' information-seeking behaviour and the use of electronic information resources (EIRs) on academic performance in Federal Universities in Northeastern of Nigeria research in this aspect has stalled in the region. To address the prevalent and worrying issues among the undergraduate students' low information-seeking and underutilization of EIRs, an exploratory research approach has been adopted. These issues significantly impact students' information-seeking behaviour on their academic performance by utilizing electronic information resources. Hence, prioritizing undergraduate students in maintaining their individuality by enhancing, maintaining, and nurturing their mindset in utilizing EIRs for academic purposes can be advantageous for academic institutions, faculty, and students. These resources and services are primarily intended to help them complete their academic tasks. The study concludes by revealing mixed and conflicting findings, among the limited information-seeking behavior and under-utilization of electronic information resources.